Entre peste et famine : caractérisation d’une crise de mortalité par l’étude de trois sépultures multiples du site de Kutná Hora – Sedlec (République tchèque, XIVe siècle) - Auxane de Lépinau; Dominique Castex; Hana Brzobohatá; Jan Frolík; Filip Velímský; Jaroslav Brůžek; Petr Velemínský; Sacha Kacki (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
The later centuries of the Middle Ages were a time of recurrent epidemics and famines, some of which caused such huge mortality that mass graves and emergency burial grounds had to be created. Several anthropological studies have investigated these graves and cemeteries, but only a few have attempted to assess the bioarchaeological features that could distinguish between these two types of crisis. Our study tackles this question through an anthropological and palaeopathological study of three 14th century mass graves at Kutná Hora – Sedlec (Czech Republic), for which historical data support a relationship with either a famine or the Black Death. Data on the 68 skeletons recovered from these graves were compared with data on 284 skeletons from a local mediaeval cemetery (Sedlec Cathedral) and with a set of reference data documenting plague and famine mortality. The results reveal differences in age structure, osteometrics and pre-existing health status between the catastrophic and attritional assemblages. The general pattern of non-adult mortality, the value of certain demographic indices and the pattern of skeletal lesions in the mass graves investigated align more closely with the reference data for plague mortality, making their link with the Black Death the most likely scenario. Although a definite diagnosis will require further analysis, this study offers the first evidence of features that might distinguish between these two types of crisis, paving the way for future research on past epidemics and famines.